2020
DOI: 10.1101/2020.02.07.939199
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dual blockade of IL-6 and CTLA-4 regresses pancreatic tumors in a CD4+T cell-dependent manner

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is exceptionally resistant to immune checkpoint inhibition (ICI). We previously reported that elevated systemic interleukin-6 (IL-6) and increased numbers of T cells positive for circulating cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) correlate with worse overall survival in patients with PDAC. We postulated that combined blockade of IL-6 and CTLA-4 would significantly enhance anti-tumor immune responses to PDAC. Dual blockade of IL-6 and CTLA-4 in immune compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
(39 reference statements)
1
1
0
Order By: Relevance
“…In these experiments, we used a suboptimal dose of anti-CTLA4 and anti-PD-1 antibody so we might measure the additive effect of all therapeutic factors. Improvement of ICB treatment in the context of IL-6 blockade [18][19][20]28] and the detrimental effect of IL-6 in response to ICB has previously been described [29] , as well as the additive effect of SMG1 inhibition with ICB treatment (Fig. S3I).…”
Section: Smg1 Is Upregulated In An Inflammatory Context By the Il-6/s...supporting
confidence: 52%
“…In these experiments, we used a suboptimal dose of anti-CTLA4 and anti-PD-1 antibody so we might measure the additive effect of all therapeutic factors. Improvement of ICB treatment in the context of IL-6 blockade [18][19][20]28] and the detrimental effect of IL-6 in response to ICB has previously been described [29] , as well as the additive effect of SMG1 inhibition with ICB treatment (Fig. S3I).…”
Section: Smg1 Is Upregulated In An Inflammatory Context By the Il-6/s...supporting
confidence: 52%
“…Tocilizumab is useful for dealing with adverse events secondary to other types of immunotherapy ( Kotch et al., 2019 ). Preclinical data have found that combined blockade of IL-6R and CTLA-4 enhances the antitumor responses in murine pancreatic tumor models, indicating that IL-6R blockade in combination with ICIs in the clinical settings have the potential to augment efficacy and limit irAEs ( Ware et al., 2019 , Ware et al, 2020 ). Mycophenolate mofetil is a purine antagonist that inhibits lymphocyte proliferation and is used as a second-line immunosuppressive drug ( Brahmer et al., 2018 ).…”
Section: Efforts To Uncouple Antitumor Immunity From Inflammation-drimentioning
confidence: 99%